A superhard, wear-resistant, high-entropy coating, its preparation method, and its application.
By forming a layered TiAlCrMoTa metal transition layer and TiAlCrMoTaSiN composite superhard coating on the surface of the substrate, using high-entropy alloys and amorphous/nano-crystalline structures, the existing coating has been solved by using low hardness and insufficient bonding strength, and a coating with high hardness and wear resistance is achieved, which is suitable for a variety of high-performance materials.
Patent Information
- Application Number
- CN202410547557.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-06
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-05-06
AI Technical Summary
The existing super-hard wear-resistant coating has low hardness and insufficient bonding strength with the substrate, resulting in insufficient wear resistance of the coating.
The layered TiAlCrMoTa metal transition layer and TiAlCrMoTaSiN composite superhard coating are used to form a high-entropy alloy coating through high-power pulse magnetron sputtering technology, which enhances the binding force between the substrate and the coating, and strengthens the hardness and friction resistance of the coating through high entropy effect and amorphous/nano-crystal structure.
It significantly improves the hardness and wear resistance of the coating, enhances the bonding force between the substrate and the coating, solves the problems of low hardness and insufficient bonding strength, and is suitable for wear-resistant and corrosion-resistant materials and tool materials.
Smart Images

Figure CN118441242B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material surface coating, and in particular to a superhard wear-resistant high-entropy coating and a preparation method and application thereof. Background Art
[0002] As a material with high hardness and wear resistance, high-speed steel has good toughness and can be used to manufacture cutting tools. It is widely used in machinery, tools, automobiles, aviation, and microelectronics processing. High-speed steel turning tools are usually manufactured as a whole, and the main cutting edge collapses during processing. At the same time, the tool is very prone to excessive wear or even fracture failure. Depositing a hard coating on the surface of the material through corresponding technology can significantly improve the hardness, toughness, corrosion resistance and friction performance of the base material and the high-temperature service life without damaging the original performance of the base material. In the precision machining industry, the coating can not only increase the service life of the material, but also improve the material processing accuracy and product surface quality. In addition, the preparation of a hard coating on the surface of metal products can significantly improve the material's high-temperature erosion resistance and high-temperature oxidation resistance. Therefore, hard coatings are widely used in machinery, tools, automobiles, aviation, and microelectronics processing.
[0003] At present, researchers at home and abroad focus on the optimization of the composition and structural design of superhard wear-resistant coatings in order to develop more multi-component superhard coatings with excellent performance, but the problem of low hardness still exists. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a superhard wear-resistant high entropy coating and a preparation method and application thereof. The high entropy coating of the present invention has high hardness.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The invention provides a superhard wear-resistant high entropy coating, comprising a stacked TiAlCrMoTa metal transition layer and a TiAlCrMoTaSiN composite superhard coating.
[0007] Preferably, the composition of the TiAlCrMoTa metal transition layer is as follows: Ti 19at%, Al 21at%, Cr 22at%, Mo 18at%, Ta 20at%.
[0008] Preferably, the thickness of the TiAlCrMoTa metal transition layer is 0.1 μm.
[0009] Preferably, the TiAlCrMoTaSiN composite superhard coating comprises the following percentages of elements: 47-51 at%, Si 0-3 at%, N 48-50 at%, and the metal elements include Ti, Al, Cr, Mo and Ta.
[0010] Preferably, the thickness of the TiAlCrMoTaSiN composite superhard coating is 1-3 μm.
[0011] The present invention also provides a method for preparing the superhard wear-resistant high entropy coating described in the above technical solution, comprising the following steps:
[0012] High-power pulsed magnetron sputtering is performed on the surface of the substrate to sequentially form the TiAlCrMoTa metal transition layer and the TiAlCrMoTaSiN composite superhard coating to obtain the superhard wear-resistant high-entropy coating.
[0013] Preferably, the high-power pulsed magnetron sputtering conditions for forming the TiAlCrMoTa metal transition layer include: a deposition temperature of 300 to 450°C, an argon gas flow rate of 20 to 40 sccm, a gas purity of >99.999%, a pressure of 0.1 to 0.35 Pa, a power supply of 0 to 300 W, a bias voltage of -80 to -150 V, and a deposition time of 5 to 10 min.
[0014] Preferably, the high-power pulsed magnetron sputtering conditions for forming the TiAlCrMoTaSiN composite superhard coating include: a deposition temperature of 300-450°C, an argon flow rate of 20-35sccm, a nitrogen flow rate of 5-15sccm, and a pressure of 0.2-0.45Pa; the alloy target is sputtered using a HIPIMS power supply with a power of 150-300W, the Si target is sputtered using a radio frequency power supply with a power of 0-150W, a bias voltage of -80--150V, and a deposition time of 2-4h.
[0015] Preferably, the alloy target is an alloy target of Al, Cr, Mo, Ta and Ti with equal atomic ratios, the power pulse width is 50 μs, the frequency is 870 Hz, and the pulse negative voltage is -850V.
[0016] The present invention also provides the application of the superhard wear-resistant high-entropy coating described in the above technical solution or the superhard wear-resistant high-entropy coating prepared by the preparation method described in the above technical solution in the fields of machinery, tools and molds, automobiles, aviation and microelectronics processing.
[0017] The invention provides a superhard wear-resistant high entropy coating, comprising a stacked TiAlCrMoTa metal transition layer and a TiAlCrMoTaSiN composite superhard coating.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The coating of the present invention comprises a TiAlCrMoTa metal transition layer and a TiAlCrMoTaSiN composite superhard coating, wherein the TiAlCrMoTa metal transition layer can effectively enhance the bonding between the substrate and the coating, improve the bonding between the hard coating and the metal substrate, and the TiAlCrMoTaSiN composite superhard coating can increase the bonding between the coating and the substrate, and simultaneously utilizes the high entropy effect including increasing the compatibility between elements, inducing the lattice distortion effect, the cocktail effect between Ti, Al, Cr, Mo and Ta elements, and the hysteresis diffusion effect of reducing the diffusion rate of elements, and combines the amorphous / nanocrystalline composite structure strengthening effect composed of a-Si3N4 amorphous structure and ordinary TiAlCrMoTaN nanocrystalline structure to improve the hardness and friction resistance of the coating, thereby solving the problems of low hardness, low bonding strength with the substrate, and insufficient wear resistance of the coating of ordinary hard coatings. The coating of the present invention has high oxidation resistance, high hardness, high wear resistance, and high substrate-coating bonding, and is a coating with excellent comprehensive performance, which is suitable for wear-resistant and corrosion-resistant materials and tool materials, etc.
[0020] The present invention also provides a method for preparing the superhard, wear-resistant, high-entropy coating described in the above technical solution, which adopts HIPIMS magnetron sputtering technology (high power pulsed magnetron sputtering) and utilizes a multi-element alloy target, thereby realizing integrated preparation and shortening the process flow; and a single multi-element alloy target is beneficial to maintaining the stability of the coating composition and structure. At the same time, the process technology is mature, low-cost and basically does not cause harm to the environment and human health. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The grazing incidence GIXRD patterns of the ultra-hard wear-resistant high entropy coating prepared in Example 1 under different bias conditions;
[0022] Figure 2 This is a SEM image of the cross section of the superhard wear-resistant high entropy coating prepared in Example 1;
[0023] Figure 3 Nanoindentation test results of the ultra-hard wear-resistant high entropy coating prepared in Example 1;
[0024] Figure 4 Friction curve variation curve of the CrAlN coating and the superhard wear-resistant high entropy coating prepared in Example 1 under 5N load condition;
[0025] Figure 5 The ultra-hard wear-resistant high entropy coating prepared in Example 1 was oxidized at 800°C for 20 hours. Figure 5 a) and cross-sectional morphology (see Figure 5 (b) DETAILED DESCRIPTION
[0026] The invention provides a superhard wear-resistant high entropy coating, comprising a stacked TiAlCrMoTa metal transition layer and a TiAlCrMoTaSiN composite superhard coating.
[0027] In the present invention, the composition of the TiAlCrMoTa metal transition layer is preferably as follows: Ti 19at%, Al 21at%, Cr 22at%, Mo 18at%, Ta 20at%.
[0028] In the present invention, the thickness of the TiAlCrMoTa metal transition layer is preferably 0.1 μm.
[0029] In the present invention, the TiAlCrMoTaSiN composite superhard coating preferably includes the following percentages of elements: metal elements 47-51at%, Si 0-3at%, N 48-50at%, and the metal elements preferably include Ti, Al, Cr, Mo and Ta.
[0030] In the present invention, the content of Si in the TiAlCrMoTaSiN composite superhard coating is preferably 2 at %.
[0031] In the present invention, the content of N in the TiAlCrMoTaSiN composite superhard coating is preferably 48 at %.
[0032] In the present invention, the metal elements in the TiAlCrMoTaSiN composite superhard coating preferably constitute a high entropy alloy, and the contents of Ti, Al, Cr, Mo and Ta in the TiAlCrMoTaSiN composite superhard coating are independently preferably 8 to 11 at%.
[0033] In the present invention, the TiAlCrMoTaSiN composite superhard coating preferably includes the following percentages of elements: Ti 10at%, Al 10at%, Cr 10at%, Mo 10at%, Ta 10at%, Si 2at%, N 48at%.
[0034] In the present invention, the thickness of the TiAlCrMoTaSiN composite superhard coating is 1 to 3 μm.
[0035] The present invention also provides a method for preparing the superhard wear-resistant high entropy coating described in the above technical solution, comprising the following steps:
[0036] High-power pulsed magnetron sputtering is performed on the surface of the substrate to sequentially form the TiAlCrMoTa metal transition layer and the TiAlCrMoTaSiN composite superhard coating to obtain the superhard wear-resistant high-entropy coating.
[0037] In the present invention, the substrate is preferably high speed steel.
[0038] In the present invention, the substrate is preferably polished before high-power pulse magnetron sputtering, and then ultrasonically cleaned with acetone solvent and dried.
[0039] The present invention preferably mounts the substrate on a sample stage of a rotating rack, starts a magnetron sputtering device to evacuate and then heat, introduces argon gas and starts a bias cleaning power supply, performs ion bombardment cleaning on the substrate, and turns off the bias power supply after cleaning is completed.
[0040] In the present invention, the ion bombardment cleaning preferably includes the following steps: using a molecular pump to pump the vacuum degree of the vacuum chamber to 1.0×10 -3 Pa or less (preferably 9.0×10 -4 Pa), the heating temperature is 300-450°C (preferably 400°C), high-purity argon gas with a purity of 99.99% is introduced, the argon gas flow rate is 80-120sccm (preferably 110sccm), the vacuum chamber pressure is maintained at 0.8-1.1Pa (preferably 1.0Pa), the cleaning bias is -800V--1000V (preferably -900V), and the cleaning time is 8-15min.
[0041] In the present invention, during the high-power pulsed magnetron sputtering, the distance between the target and the sample is preferably 7 cm, the high entropy alloy target is preferably installed at the HIPIMS power target position, and the Si target is preferably installed at the RF power target position.
[0042] In the present invention, the high-power pulsed magnetron sputtering conditions for forming the TiAlCrMoTa metal transition layer preferably include: a deposition temperature of 300 to 450°C (preferably 400°C), an argon gas flow rate of 20 to 40 sccm (preferably 30 sccm), a gas purity of >99.999%, a pressure of 0.1 to 0.35 Pa (preferably 0.2 Pa), a power supply of 0 to 300 W (preferably 150 W), a bias voltage of -80 to -150 V (preferably -100 V), and a deposition time of 5 to 10 min.
[0043] In the present invention, when forming the TiAlCrMoTa metal transition layer, the alloy target is preferably an alloy target of Al, Cr, Mo, Ta and Ti with equal or nearly equal atomic ratios, the power pulse width is preferably 50μs, the frequency is preferably 870Hz, and the pulse negative voltage is preferably -850V.
[0044] After forming the TiAlCrMoTa metal transition layer, the present invention preferably turns off the bias power supply and the sputtering power supply.
[0045] In the present invention, the high-power pulsed magnetron sputtering conditions for forming the TiAlCrMoTaSiN composite superhard coating preferably include: a deposition temperature of 300 to 450°C, an argon flow rate of 20 to 35 sccm (preferably 24 sccm), a nitrogen flow rate of 5 to 15 sccm (preferably 10 sccm), and a pressure of 0.2 to 0.45 Pa; the alloy target is sputtered using a HIPIMS power supply with a power of 150 to 300 W, the Si target is sputtered using a radio frequency power supply with a power of 0 to 150 W (preferably 80 W), a bias voltage of -80 to -150 V (preferably -125 V), and a deposition time of 2 to 4 h.
[0046] After forming the TiAlCrMoTaSiN composite superhard coating, the present invention preferably turns off the bias power supply and the sputtering power supply, waits for the vacuum chamber temperature to naturally drop to room temperature, opens the vacuum chamber and takes out the sample to obtain the superhard wear-resistant high entropy coating.
[0047] In the present invention, the purity of the gases used is independently preferably >99.999%.
[0048] The present invention also provides the application of the superhard wear-resistant high-entropy coating described in the above technical solution or the superhard wear-resistant high-entropy coating prepared by the preparation method described in the above technical solution in the fields of machinery, tools and molds, automobiles, aviation and microelectronics processing.
[0049] The present invention has no particular limitation on the specific manner of the application, and any manner familiar to those skilled in the art may be used.
[0050] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] Example 1
[0052] Step 1: First, the substrate surface is polished, then ultrasonically cleaned and dried using acetone solvent. The target is 7 cm away from the sample, where the high entropy alloy target is installed at the HIPIMS power target position and the Si target is installed at the RF power target position;
[0053] Step 2: Install the dried metal sample on the sample stage of the rotating rack, turn on the power of the sputtering equipment, and use a molecular pump to pump the vacuum degree of the vacuum chamber to 9.0×10 -4Pa, and then heat the sample stage to 400 ° C. Introduce high-purity argon gas with a purity of 99.99% into the vacuum chamber, set the argon gas flow rate to 110 sccm, and maintain the vacuum chamber pressure at 1.0 Pa. Turn on the bias cleaning power supply, set the cleaning bias to -900V, perform ion bombardment cleaning on the substrate, set the cleaning time to 15min, and turn off the bias power supply after cleaning is completed;
[0054] Step 3: Reduce the argon input flow rate to 30sccm, the corresponding gas pressure is 0.2Pa, set the deposition bias to -100V, turn on the bias power supply, set the HIPIMS target power to 150W, set the sputtering time to 10min, the power pulse width to 50μs, the frequency to 870Hz, the pulse negative voltage to -850V, and deposit a TiAlCrMoTa transition layer on the metal surface. After the deposition is completed, turn off the power supply to form a TiAlCrMoTa metal transition layer with a composition of Ti 19at%, Al 21at%, Cr 22at%, Mo 18at%, Ta20at%;
[0055] Step 4: nitrogen is introduced, and appropriate nitrogen and argon flow rates are adjusted. Argon with a gas flow rate of 24 sccm and high-purity nitrogen with a gas flow rate of 10 sccm are introduced. The gas purity is >99.999%. The corresponding pressure of the vacuum chamber is 0.2 Pa. The alloy target power supply power is set to 200 W, the power pulse width is 50 μs, the frequency is 870 Hz, and the pulse negative voltage is -850 V. The Si target is sputtered using a radio frequency target power supply, the power is set to 80 W, the bias voltage is set to 0 to -125 V, the deposition time is set to 2 h, and the bias power supply and sputtering power supply are turned on to deposit a TiAlCrMoTaSiN coating on the substrate surface;
[0056] Step 5: After the temperature of the vacuum chamber drops to room temperature, open the vacuum chamber and take out the sample. The coating obtained on the surface of the sample is a super-hard, wear-resistant, high-entropy coating of a TiAlCrMoTa metal transition layer + TiAlCrMoTaSiN composite super-hard coating.
[0057] The structural performance of the superhard wear-resistant high entropy coating prepared in this example was tested.
[0058] Figure 1 The grazing incidence GIXRD patterns of the coating under different bias conditions show that after the bias is applied, the coating exhibits a face-centered cubic solid solution structure and the (200) orientation is significantly enhanced.
[0059] Figure 2The SEM images of the cross section of the superhard wear-resistant high-entropy coating prepared at a bias voltage of -100 V at different magnifications show that the coating is composed of dense columnar crystals. The overall thickness of the coating is 1.6 μm. The surface of the prepared coating is dense and smooth, and no defects such as large particles or pits are found. The element content of the TiAlCrMoTaSiN composite superhard coating is detected by EDS, which are Ti 9at%, Al 11at%, Cr 11at%, Mo 9at%, Ta 10at%, Si 2at%, and N48at%.
[0060] The hardness of the ultra-hard wear-resistant high entropy coating prepared at a bias voltage of -100V was tested using a nanoindenter. The results are shown in Figure 3 , it can be seen that the hardness of the coating reaches above 40GPa.
[0061] Figure 4 The changes in the friction curves of the CrAlN coating and the ultra-hard wear-resistant high-entropy coating prepared under a load of 5N and a bias voltage of -100V show that the friction coefficient of the material is reduced from 0.69 to 0.56 after coating with the high-entropy wear-resistant hard coating.
[0062] Figure 5 The ultra-hard wear-resistant high entropy coating prepared at a bias voltage of -100 V was oxidized at 800℃ for 20h. Figure 5 a) and cross-sectional morphology (see Figure 5 In b), it can be seen that the oxide layer on the coating surface is dense. At this temperature, a thin oxide layer is formed on the surface of the coating, which effectively inhibits the oxidation of the coating.
[0063] In summary, after coating the surface of high-speed steel with a superhard and wear-resistant high-entropy coating, the hardness and wear resistance of the material are significantly improved, and the coating has good antioxidant properties.
[0064] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A superhard wear-resistant high entropy coating, characterized in that: Specifically, it is a stacked TiAlCrMoTa metal transition layer and a TiAlCrMoTaSiN composite superhard coating; the composition of the TiAlCrMoTa metal transition layer is as follows: Ti 19at%, Al 21at%, Cr 22at%, Mo 18at%, Ta 20at%; the element content of the TiAlCrMoTaSiN composite superhard coating is Ti 9at%, Al 11at%, Cr 11at%, Mo 9at%, Ta 10at%, Si 2at%, N 48at%.
2. The superhard wear-resistant high entropy coating according to claim 1, characterized in that: The thickness of the TiAlCrMoTa metal transition layer is 0.1 μm.
3. The superhard wear-resistant high entropy coating according to claim 1, characterized in that: The thickness of the TiAlCrMoTaSiN composite superhard coating is 1-3 μm.
4. The method for preparing the superhard wear-resistant high entropy coating according to any one of claims 1 to 3, characterized in that: The following steps are involved: Performing high-power pulsed magnetron sputtering on the surface of the substrate to sequentially form the TiAlCrMoTa metal transition layer and the TiAlCrMoTaSiN composite superhard coating to obtain the superhard wear-resistant high entropy coating; The high-power pulsed magnetron sputtering conditions for forming the TiAlCrMoTa metal transition layer include: a deposition temperature of 300 to 450° C., an argon gas flow rate of 20 to 40 sccm, a gas purity of >99.999%, a pressure of 0.1 to 0.35 Pa, a power supply of 0 to 300 W, a bias voltage of -80 to -150 V, and a deposition time of 5 to 10 min; The alloy target is an alloy target of Al, Cr, Mo, Ta and Ti with equal atomic ratios; The high-power pulsed magnetron sputtering conditions for forming the TiAlCrMoTaSiN composite superhard coating include: a deposition temperature of 300 to 450° C., an argon flow rate of 20 to 35 sccm, a nitrogen flow rate of 5 to 15 sccm, and a pressure of 0.2 to 0.45 Pa; the alloy target is sputtered using a HIPIMS power supply with a power of 150 to 300 W, the Si target is sputtered using a radio frequency power supply with a power of 0 to 150 W, a bias voltage of -80 to -150 V, and a deposition time of 2 to 4 hours.
5. The preparation method according to claim 4, characterized in that: When the TiAlCrMoTa metal transition layer is formed, the power pulse width is 50 μs, the frequency is 870 Hz, and the pulse negative voltage is -850V.
6. Application of the superhard wear-resistant high entropy coating according to any one of claims 1 to 3 or the superhard wear-resistant high entropy coating prepared by the preparation method according to claim 4 or 5 in the fields of tooling, automobiles, aviation and microelectronics processing.
Citation Information
Patent Citations
Dispersion-strengthened high-entropy alloy nitride ceramic coating with gradient structure and preparation method of dispersion-strengthened high-entropy alloy nitride ceramic coating
CN117187747A